Impacts of different fencing periods and grazing intensities on insect diversity in the desert steppe in Inner Mongolia - Wang, Ning; Song, Xiaoxiao; Wang, Jiayu; Wang, Liming (Frontiers in Ecology and Evolution, 2022)
For the past several decades, both species biodiversity and productivity of desert steppe have been reduced due to excessive use and climate factors. To counteract this, Chinese government has supported large-scale grassland ecological restoration programs since the year 2000. The policy needs a standard for the evaluation of the effects of such restorative measures on the grasslands after decades. Grassland insect diversity plays an important role in the maintenance of plant species and functional diversity. To understand the relation of grazing management and insect diversity, we use a complete two factor design, two fencing periods (3 or 7 years) and three grazing intensities (0, 6, or 12 sheep per ha), to examine the response of the insect diversity to fencing and grazing in desert steppe. We found almost no significant differences in either plant or insect species diversity between the sites fenced for 3 and 7 years, as the pressure of grazing increased, insect diversity decreased to a greater extent at 7-year enclosure sites than at 3-year sites. We recommend the most suitable grazing intensity for the sustainability of biodiversity of the desert steppe in Inner Mongolia is light grazing (8 sheep/ha 0.5 yr−1), and the most suitable fencing period is three years, which suggest that policies that remove livestock from the desert grassland for long periods (7 + years) are not beneficial for maintaining insect diversity, and heavy grazing lead ecological environment weaker and insect diversity decreasing. Thus, periodic livestock grazing is important in the design of management actions to preserve biodiversity.